Draft Annual Plan 1973-74 Government of Uttar Pradesh - Planning Commission (Planning Commission, 1972)
The rate of economic growth in Uttar Pradesh has been painfully slow due to a variety of reasons and circumstances. One of the most important reasons is the present low agricultural productivity. the other reasons are the growing population, its overwhelming dependence on agriculture, slow rate of investment, slow rate of industrialisation and consequently high level of unemployment and under-employment.
Government of Uttar Pradesh, Planning Department